2019
DOI: 10.1016/j.margeo.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Submarine morpho-structure and active processes along the North American-Caribbean plate boundary (Dominican Republic sector)

Abstract: The northern margin of Hispaniola records the oblique collision/underthrusting of the Bahamas Carbonate Province with the island-arc. Due to the collision, northern Hispaniola has suffered several natural disasters caused by major earthquakes and tsunamis, such as the historic earthquake of 1842, the tsunami caused by earthquake-driven slumping in 1918 in the Mona Passage, the seismic crisis of 1943-1953 with five events of M>7.0 or the seismic crisis of 2003 with a main shock of M6.3 and a large aftershock of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 67 publications
0
14
0
3
Order By: Relevance
“…While these events are far outside our network and have large location uncertainties, it seems clear that the two most seismically active faults in this region are the SOFZ and the North Hispaniola fault, which lies offshore to the north. Rodriguez et al () also observed similarly high levels of seismicity associated with these faults; however, while the North Hispaniola fault has been mapped offshore (Rodríguez‐Zurrunero et al, ), there is still much work needed to fully characterize the structure of the SOFZ which bisects much of the northern Dominican Republic onshore. The present day seismicity highlights the seismic hazard potential of the northern edge of the Caribbean‐North American plate boundary, which can also be seen by the >M w 7.0 historical earthquakes associated these faults (Prentice et al, ; ten Brink et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While these events are far outside our network and have large location uncertainties, it seems clear that the two most seismically active faults in this region are the SOFZ and the North Hispaniola fault, which lies offshore to the north. Rodriguez et al () also observed similarly high levels of seismicity associated with these faults; however, while the North Hispaniola fault has been mapped offshore (Rodríguez‐Zurrunero et al, ), there is still much work needed to fully characterize the structure of the SOFZ which bisects much of the northern Dominican Republic onshore. The present day seismicity highlights the seismic hazard potential of the northern edge of the Caribbean‐North American plate boundary, which can also be seen by the >M w 7.0 historical earthquakes associated these faults (Prentice et al, ; ten Brink et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Haiti is bisected by two major left‐lateral strike‐slip faults, the Septentrional‐Oriente fault zone (SOFZ) in the north, which has been mapped offshore (Calais & Mercier de Lépinay, ; Leroy et al, ; Rodríguez‐Zurrunero et al, ), and the EPGF in the south (Figure ; Mann et al, ). Between these faults, the fold and thrust belt, known as the Trans‐Haiti belt and active in the Miocene and Pliocene, controls much of the relief on Haiti (Pubellier et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This fault accommodated the left‐lateral component of the plate convergence, revealing active strain partitioning along the oblique plate boundary to the northwest of Barbuda (Laurencin et al., 2019; ten Brink & Lin, 2004). Farther west, at the Puerto Rico and the Virgin Islands (PRVI) Margin, the Bunce and Bowin left‐lateral strike‐slip faults connect to the northern Hispaniola lithospheric transpressive faults, which bound the Bahamas Bank–Hispaniola collisional system (Mann et al., 2005; Rodríguez‐Zurrunero et al., 2019; ten Brink & Lin, 2004).…”
Section: Geological Settingsmentioning
confidence: 99%
“…3). That indicates that the thicker crust of the BCP cannot truly subducts beneath the CARIB plate (Dolan et al, 1998;Rodríguez-Zurrunero et al, 2019).…”
Section: Oblique Collision Domain (Ocd)mentioning
confidence: 99%